Vitamin D deficiency and adverse body composition in adolescents - Bo Wang; Songting Gao; Zhongxin Zhu (Journal of Orthopaedic Surgery and Research)
Abstract Background Vitamin D deficiency is a global public health concern, particularly among adolescents. While its skeletal effects are well-established, evidence on its extraskeletal roles in muscle and adipose tissue during this critical developmental period remains limited, especially using direct body composition measures. Methods We analyzed 3,648 participants aged 12–19 years from NHANES data (2011–2018), stratifying vitamin D status as deficiency, insufficiency, or sufficiency. Multivariable linear regression models evaluated associations with appendicular lean mass index (ALMI), visceral adipose tissue area (VATA), and total bone mineral density (BMD). Subgroup analyses explored age, sex, and racial/ethnic variations. Results Vitamin D deficiency/insufficiency affected 40.1% of participants. Higher serum vitamin D status correlated with positive body composition: lower VATA (β = -0.092, 95% CI: -0.124 to -0.061), and higher ALMI (β = 0.005, 95% CI: 0.004 to 0.006) and BMD (β = 0.0008, 95% CI: 0.0006 to 0.0010). Subgroup analyses revealed stronger ALMI associations in older boys and Mexican Americans, while VATA reductions were most pronounced in younger girls. BMD benefits were consistent across subgroups. Conclusions Vitamin D deficiency is prevalent among adolescents and independently associated with unfavorable body composition, modulated by demographic factors. These findings highlight the need for targeted interventions to optimize musculoskeletal and metabolic health during this developmental window.